Implementasi Algoritma C4.5 untuk Medeteksi Golongan Penderita Covid-19 Berdasarkan Gejala dan Penyebabnya - Efani Desi; Siti Aliyah (KITA Institute, 2023)
Corona virus disease/Covid-19 is the name given by the World Health Organization (WHO) for sufferers infected with the 2019 novel corona virus. Seeing the development of the spread of the virus which continues to increase and the rate of its spread is even faster, it has created anxiety in all circles in public. Therefore, an appropriate method is needed that can make it easier to detect Covid-19 sufferers without having to do Covid-19 RT-PCR. So that the treatment of patients can be handled properly. The author uses the C4.5 Algorithm method which can predict whether the patient has Covid-19 based on the symptoms and causes. The results of this study researchers used the RapidMiner application to apply the C4.5 Algorithm method so that the results obtained showed an accuracy value of 70% for Covid-19 sufferers. So that with this research the public can self-detect and treat the symptoms of Covid-19 suffered if the patient belongs to the ODP group, the action that must be taken is to self-isolate for 14 days to carry out the recommended treatment and to avoid spreading the virus to the surrounding environment, so as well as other patient groups.